Spatial modulation of motor-sensory recalibration in early deaf individuals. (28th July 2017) - Vercillo, Tiziana; Jiang, Fang
Abstract: Audition dominates other senses in temporal processing, and in the absence of auditory cues, temporal perception can be compromised. Moreover, after auditory deprivation, visual attention is selectively enhanced for peripheral visual stimuli. In this study, we assessed whether early hearing loss affects motor-sensory recalibration, the ability to adjust the timing of an action and its sensory effect based on the recent experience. Early deaf participants and hearing controls were asked to discriminate the temporal order between a motor action (a keypress) and a visual stimulus (a white circle) before and after adaptation to a delay between the two events. To examine the effects of spatial modulation, we presented visual stimuli in both central and peripheral visual fields. Results showed overall higher temporal JNDs (Just Noticeable Difference) for deaf participants as compared to hearing controls suggesting that the auditory information is important for the calibration of motor-sensory timing. Adaptation to a motor-sensory delay induced distinctive effect in the two groups of participants, with hearing controls showing a recalibration effect for central stimuli only whereas deaf individuals for peripheral visual stimuli only. Our results suggest that auditory deprivation affects motor-sensory recalibration and that the mechanism underlying motor-sensory recalibration is susceptible to spatial modulation. Highlights: Early auditory loss affects motor-sensory integration. Adaptation to a motor-sensory delay induced opposite effect in deaf and hearing individuals. Hearing controls show a recalibration effect for central but not peripheral stimuli. Deaf individuals show a recalibration effect for peripheral visual stimuli only. Motor-sensory recalibration is susceptible to spatial modulation. Early auditory deprivation compromises precision in sensory-motor temporal judgments.